PENGARUH KESEHATAN DAN KESELAMATAN KERJA TERHADAP SEMANGAT KERJA DAN PRESTASI KERJA KARYAWAN DIPT. RAMAJAYA PRAMUKTI KABUPATEN KAMPAR - Rusmayani '; Susi Hendriani; T. Firli Musfar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The research was conducted atPT. Ramajaya Pramukti Kabupaten Kampar. With the aim to identify and analyze The Effect Of Health And Safety On The Spirit Of Work And Achievement Employees In PT. Ramajaya Pramukti Kabupaten Kampar. Where in this study population was all employees at PT. Ramajaya Pramukti Kabupaten Kampar totaling 121 people. The sample used in this study were 121 employees and data processing using path analysis with SPSS.Based on the test results if the data using path analysis can be drawn some conclusions, namely: There are influence which of signifikan among Health And Safety to spirit of work employees in PT. Ramajaya Pramukti Kabupaten Kampar. If problem of working safety and health don’t be managed better hence will will lessen the spirit of work employees. Problems of employees working safety and health seen from: Equipments and supply of work exist in company not yet fully awake better, Employees very easy hit by disease in working. There are influence which is signifikan among health variable and working safety to employees labour capacity in PT. Ramajaya Pramukti Kabupaten Kampar. If employees labour capacity don’t be improved by hence will affect ugly to company. So also on the contrary if company or organization can realize healthy and balmy work atmosphere hence will be able to improve labour capacity all its employees. Variable spirit of work represent variable having an effect on dominant to employees labour capacity. From result of perception which writer conduct seen that spirit of work employees at PT. Ramajaya Pramukti Kabupaten Kampar still not yet is maximal so cause their labour capacity become to lower.Keyword: Health and Safety, Spirit, and Achievement Employees.